2001
DOI: 10.1253/jcj.65.242
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Pacing During Radiofrequency Ablation of Junctional Ectopic Tachycardia

Abstract: ecause of its refractoriness to medical therapy and the high mortality rate, 1,2 junctional ectopic tachycardia (JET) has been treated by ablation of the atrioventricular (AV) junction using either direct 1 or radiofrequency (RF) current. 3,4 However, these therapies may result in the need for permanent cardiac pacing. Recently, selective ablation of the JET focus while preserving normal AV conduction was reported, [5][6][7][8][9] suggesting that the junctional focus is usually perinodal and that ablative lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…It is beneficial to preserve the AV conduction by performing atrial pacing during the energy application 17 or delivering the application from a low-dose energy 18 . In our case, monitoring the AV conduction by atrial pacing contributed to preventing CAVB.…”
Section: Discussionmentioning
confidence: 76%
“…It is beneficial to preserve the AV conduction by performing atrial pacing during the energy application 17 or delivering the application from a low-dose energy 18 . In our case, monitoring the AV conduction by atrial pacing contributed to preventing CAVB.…”
Section: Discussionmentioning
confidence: 76%
“…JET is considered a rare arrhythmia presenting at the ECG with narrow ventricular complexes, AV dissociation, and QRS morphology resembling that of sinus beats 1–18 . Invasive electrophysiology has demonstrated that each ventricular electrogram is preceded by a “leading” His bundle deflection with an HV interval that has to be compatible with ante grade conduction (> 35 ms) 1–3,14,15 …”
Section: Discussionmentioning
confidence: 99%
“…As for the clinical presentation, JET appears more often incessant than paroxysmal and as a result it frequently causes hemodynamic impairment 1–20 . Most of the collected evidence relates JET electrophysiological mechanism to enhanced automaticity due to a focus located on the AV junction and this might also explain JET sensitivity to cathecolamines 1–20 . Class IC antiarrhythmic agents, amiodarone, and β‐blockers may be regarded as possible therapeutic options, although a decrease in ventricular rate rather than a complete resolution of the arrhythmia should be expected, since sinus rhythm restoration may not be accomplished in several cases 2,4–7,9,13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations